إدارة الموارد البشرية والأداء التنظيمي: - العلاقة وآليات التأثير- - بوباكور, فارس; عقون, سهام (جامعة الوادي - University of Eloued, 2017)
بعد الوقوف على الأداء التنظيمي من مفهوم وقياس والتعريف بالموارد البشرية كأهم مصدر للميزة التنافسية المستدامة، تم التطرق في هذه الورقة البحثية الى طبيعة العلاقة والأثر بين ادارة الموارد البشرية والأداء التنظيمي التي أثبتتها الدراسات الأكاديمية النظرية والتجريبية وقد تبين من خلال هذه الورقة أن الطريقة التي يتم بها إدارة الموارد البشرية في المنظمة لها علاقة كبيرة بأدائها، ومع ذلك، لا تزال المعلومات المتوفرة حول هذه العلاقة الأساسية محدودة. After reviewing the on the concept and measurement of organizational performance, and identify human resources as the most important source of sustainable competitive advantage, it has been addressed in this paper, to the nature of the relationship and the impact between human resource management and organizational performance, which is proven by theoretical and experimental academic studies. It was found through this paper that the way in which, human resources are managed in the organization has a great relationship on performance, however, the information available on this fundamental relationship is still limited.
مقال
Keywords: الأداء التنظيمي، ممارسات ادارة الموارد البشرية ، الميزة التنافسية المستدامة; organizational performance, human resources management practices, Sustainable Competitive Advantage